NATIONAL STEREOTYPES OF THE EAST (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article examines the national stereotypes typical of Eastern countries, their origins, characteristics, and role in intercultural communication. Special attention is given to the influence of historical, religious, and cultural factors on the formation of persistent perceptions about Eastern peoples. The paper also analyzes how these stereotypes are perceived both by the carriers of Eastern culture themselves and by representatives of the West. The study addresses the issue of stereotyping in the context of globalization and intercultural dialogue, highlighting both the positive and negative aspects of the impact of national stereotypes on the perception of the East in the modern world.